The shape of general hospital nursing: the division of labour at work - Allen, Davina (1996)
This thesis is about nursing work and the ways in which nurses in a general hospital accomplished occupational jurisdiction. It is based on ethnographic data generated on a surgical ward and a medical ward in a single NHS trust hospital. The study is set in the context of recent developments in nursing and medical education (DHSS, 1987; GMC, 1993; UKCC, 1987) and health policy (DH, 1989) which have created the impetus for shifts in the division of labour in health care, reviving deep-rooted historical tensions between professional and service versions of nursing.